Distribution of the areas and heights of the radar echoes from convective clouds around Delhi during monsoon season - CHATTERJEE, R. N.; PRAKASH , PREM; ALI, KAUSHAR (MAUSAM, 1992)
Distributions of areas and heights of radar echoes from convective clouds, observed in Delhi region during six monsoon seasons, 1967-1972, were studied. Stratification of the echoes according to their areas into three different scales, namely scale D scale(<100 km2), C scale (101-1000 km2) and B/C scale (> 1000 km2) indicated predominance of the echoes in D scale, with relatively small percentage in. C and B/C scales. Frequency distributions of areas and heights of these echoes tended to be lognormally distributed.